Survivin and AURKA, key determinants of mitotic cell fate - Abdelkabir, Hana (2024)
Defects in chromosomal segregation and genome stability are two of the main hallmarks of cancer and their occurrence can often be due to aberrant expression of cell cycle regulators. Survivin is a multi-interactor protein that play fundamental dual roles as a regulator of cell division and an inhibitor of apoptosis. The family of Aurora kinases (AURKs) are amongst the many interactors that associate with survivin during mitosis, which in mammals, comprises Aurora kinase A (AURKA), Aurora kinase B (AURKB) and Aurora kinase C (AURKC). Deregulation of survivin and AURKs is linked to various abnormalities in cancer cell proliferation and strongly correlated with chemoresistance. Survivin plays a substantial role in regulating proper chromosomal alignment and segregation through its cooperation with AURKB, via the chromosomal passenger complex (CPC). It can also form a complex with AURKC, that can complement AURKB mitotic function as a CPC member during mitosis. AURKA shares functional and structural similarities with AURKB/C, however, it is still unknown whether AURKA can associate with survivin. Here, we show for the first time, that AURKA binds to survivin during mitosis and regulates its function. We report that AURKA interacts directly with the BIR domain of survivin and indirectly via its C-terminus, and their interaction is at its highest during early mitosis.  We also suggest a novel function of AURKA as a regulator of AURKB expression and activity, and as a regulator of survivin localisation and function during early and late mitosis. We further show that survivin plays a major role in controlling cell fate during mitotic arrest and its mislocalisation in the absence of AURKA leads to mitotic slippage. We show that upregulating survivin levels in both normal and transformed human cells results in premature mitotic exit when AURKA is inhibited, and that AURKA activity is essential for maintaining the localisation of the checkpoint protein BubR1 at the unattached kinetochores during mitotic arrest. These finding show that elevated survivin levels in cancer provide a risk factor to inappropriate mitotic exit and genetic instability (aneuploidy), and regulating its levels may alter the approach to utilising AURKA inhibitors in cancer treatment.